A terceirização do trabalho nas facções de costura do seridó oriental potiguar (RN), 2013-2016 - Araújo, Kayck Danny Bezerra de (2017)
The Textile Industry Interiorization Program (PRÓ-SERTÃO) is a Public Politics of responsibility for the Government of the State of Rio Grande do Norte, which aims at the interiorization of textile production through fiscal incentives and creation of resources necessary for the development of the textile production chain. The objective of this dissertation is to analyze if this outsourcing of the "anchor industries" to the "sewing factions" hat emerge and / or fall within the context of this policy were responsible for precarious work in the Seridó Potiguar region. The theoretical milestone that claimed this study was based on concepts of Outsourcing, Precarious Employment and Institutional Tinkering. From then on, a qualitative research of an inductive nature was carried out based on bibliographical and documentary studies, as well as field research through visits to the sites of the sewing factions, where the application of questionnaires and interview was made that served as a basis for a systematization between the proposed theory and the observed practice. The research approach used in the case study with the municipalities of Acari and Cruzeta, located in the territory of Seridó Oriental Potiguar, state of Rio Grande do Norte, from 2013 to 2016. The results obtained point to the precariousness of labor relations in the sewing factions. Although these factions absorb part of the population, they have never propulsion of PRÓ-SERTÃO. For, even with all the investments suggested by the official speeches, it is still a program that has difficulty implementing in the Serido territory. The study concluded that the precarious employment of labor relations in the factories of the territories studied occurred with relative ease because it occurred in a territory marked by social vulnerability, with a view the existence of a reduced number of jobs – formal and informal until the creation of the factions -, and still of high rates of unemployment which allow the practice of subcontracting by companies.